1995
DOI: 10.1021/bi00002a017
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of Inhibition of the Neutrophil Respiratory Burst Oxidase by a Peptide from the C-Terminus of the Large Subunit of Cytochrome b558

Abstract: A peptide (RGVHFIF) from near the carboxyl terminus (residues 559-565) of gp91-phox, the large subunit of cytochrome b558, was previously shown to inhibit activation of the respiratory burst oxidase [Kleinberg, M. E., Malech, H. L., & Rotrosen, D. (1990) J. Biol. Chem. 265, 15577-15583]. The peptide has been proposed to compete with gp91-phox binding to p47-phox, one of the cytosolic oxidase components. In the present studies, we have used a semirecombinant system consisting of recombinant cytosolic factors (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Domain I comprises residues 559-565, which correspond to yet another region reported to participate in the interaction of Nox2 with p47 phox . This proposal was based on mapping by peptide-phage display libraries [18] and on inhibition of oxidase activation by a Nox2 peptide containing these residues [51], but careful kinetic analysis did not support the proposed mechanism of the peptide competing with Nox2 for binding of p47 phox [52].…”
Section: Location Of Domains Deduced From Clusters Of Oxidase Inhibitmentioning
confidence: 99%
“…Domain I comprises residues 559-565, which correspond to yet another region reported to participate in the interaction of Nox2 with p47 phox . This proposal was based on mapping by peptide-phage display libraries [18] and on inhibition of oxidase activation by a Nox2 peptide containing these residues [51], but careful kinetic analysis did not support the proposed mechanism of the peptide competing with Nox2 for binding of p47 phox [52].…”
Section: Location Of Domains Deduced From Clusters Of Oxidase Inhibitmentioning
confidence: 99%
“…An antibody directed against the carboxyl-terminal 13 amino acids of gp91 phox inhibits superoxide formation in the cell-free assay (29). Synthetic peptides derived from this region inhibit NADPH oxidase activity in permeabilized neutrophils (29,34) and in the cell-free oxidase assay (29,31,57 ) have been identified by alanine scanning as important for the function of this domain, based on the relative ability of alanine-substituted peptides to inhibit oxidase activity in a cell-free assay (33). However, we found that comparable alanine substitutions in the gp91 phox polypeptide resulted in either no or only a modest reduction in NADPH oxidase activity when the mutant gp91 phox was expressed in whole cells.…”
Section: Mutagenesis Of Phagocyte Flavocytochrome B 558 Gp91mentioning
confidence: 99%
“…A kinetic analysis of oxidase inhibition by 559 RGVHFIF 565 has suggested that this peptide acts as a non-competitive inhibitor (57), which might explain why many of the mutations in the gp91 phox polypeptide did not have a profound effect. Alternatively, additional sites of interaction between p47 phox and gp91 phox may obviate the requirement for an intact 559 RGVHFIF 565 domain for oxidase assembly in intact cells.…”
Section: Mutagenesis Of Phagocyte Flavocytochrome B 558 Gp91mentioning
confidence: 99%
“…However, the first sign that the a priori assumption of a competitive mechanism is risky came from the kinetic analysis of Nox2 peptide 559-565, found to inhibit oxidase activation in vitro and proposed to act by competing with Nox2 for binding of p47 phox [27,49]. Contrary to expectations, an excess of p47 phox did not suppress the effect of the peptide and kinetic analysis did not yield a competitive but a mixed pattern of inhibition [50]. A more scathing analysis of a seemingly competitive mechanism of oxidase inhibition by Nox2 peptides overlapping NADPH binding sites is offered in [37].…”
Section: Kinetic Analysis Of Inhibition By Peptidesmentioning
confidence: 99%
“…In both Nox2 and Nox4, this region binds to the cytosolic dehydrogenase region, a link that is critical for electron flow from the cytosolic (NADPH, FAD) to the membranal (hemes) redox centers. It is remarkable that Nox2 peptide 86-94, which is one of the most intensively studied and tested in several in vivo situations, and which has a potential for clinical applications, has never been subjected to a proper kinetic analysis in relation to its role as a binding site for p47 phox , such as the one applied to Nox2 peptide 559-565 [50]. It has been suggested that p47 phox might not bind directly to the B loop in Nox2 and that, in fact, the B loop-dehydrogenase region interaction affects the binding of p47 phox to the dehydrogenase region [55].…”
Section: Inhibition Of Oxidase Activity By Peptides Versus Binding Tomentioning
confidence: 99%